2017
DOI: 10.1039/c7sc03521g
|View full text |Cite
|
Sign up to set email alerts
|

Precise synthesis of unique polydopamine/mesoporous calcium phosphate hollow Janus nanoparticles for imaging-guided chemo-photothermal synergistic therapy

Abstract: A novel synthetic strategy has been developed for fabricating spherical polydopamine/mesoporous calcium phosphate (PDA/mCaP) hollow Janus nanoparticles (H-JNPs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
101
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(102 citation statements)
references
References 50 publications
1
101
0
Order By: Relevance
“…In one case, ICG was initially immobilized over the phospholipids, and further, these conjugates were coupled with conventional polymers such as PEG; e.g., ICG-PEG-DSPE [ 44 , 106 , 107 , 108 ] and ICG-PEG-DOPE [ 109 ]. Moreover, ICG was also encapsulated in the PEG framework containing terminated reactive groups such as ICG-PEG-SH [ 110 ], or ICG-PEG-NH 2 for better targeting ability [ 111 ].…”
Section: Icg-encapsulated Polymeric Compositesmentioning
confidence: 99%
“…In one case, ICG was initially immobilized over the phospholipids, and further, these conjugates were coupled with conventional polymers such as PEG; e.g., ICG-PEG-DSPE [ 44 , 106 , 107 , 108 ] and ICG-PEG-DOPE [ 109 ]. Moreover, ICG was also encapsulated in the PEG framework containing terminated reactive groups such as ICG-PEG-SH [ 110 ], or ICG-PEG-NH 2 for better targeting ability [ 111 ].…”
Section: Icg-encapsulated Polymeric Compositesmentioning
confidence: 99%
“…Indocyanine green (ICG) is an Food and Drug Administration (FDA)‐approved near‐infrared (NIR)‐absorbing dye for imaging probes; it has proven to be an effective photosensitive agent for PTT . Although various previous studies have reported on codelivering ICG and doxorubicin (DOX) for combined anticancer therapy, most of these focused on the hyperthermia‐triggered drug release and thermal ablation . The detailed mechanisms responsible for enhanced efficacy, such as the influence of hyperthermia on the functionality of chemotherapeutic drugs in cancer cells and on chemotherapeutic drug penetration into tumor tissues, remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Multifunctional Janus nanoparticles (NPs) have become a hot spot in the research field of nanomaterials in recent years. 2,3 Due to their fascinating hierarchical superstructures, Janus particles are promising candidates for a variety of high-quality applications, such as catalysis, textiles, sensors, therapeutic treatments, and imaging diagnosis. 4,5 Recently, Janus NPs have gained extensive attention in the field of chemistry and biology, resulting from combined chemical, magnetic, optical, and electronic interactions at the solid-state heterojunction of the particles.…”
Section: Introductionmentioning
confidence: 99%